A 90-day subchronic toxicity study of 5-methyl-2-phenyl-2-hexenal in F344 rats. (April 2021) - Nakamura, Kenji; Ishii, Yuji; Takasu, Shinji; Ogawa, Kumiko
Abstract: 5-Methyl-2-phenyl-2-hexenal (MPH) has been used as a flavoring agent. In the present study, we performed a subchronic toxicity study in male and female F344 rats with oral administration of MPH by gavage at 0, 8, 24 and 70 mg/kg body weight (BW)/day for 90 days. No mortality or clinical signs were observed during the experimental period. Body weight and food consumption for all treated groups of both sexes were essentially the same as for the respective control groups. Hematologic examination demonstrated significant decreases in monocyte counts for females given 24 and 70 mg/kg BW/day. However, these changes were not substantial and no related histopathological changes were observed, suggesting that these changes were not toxicologically significant. Among organ weights, the absolute and/or relative weights of testes and liver were significantly increased in the 70 mg/kg BW/day groups of males and females, respectively, but no related histopathological changes were observed, suggesting that these changes did not reflect adverse effects. In addition, no treatment-related histopathological changes were observed for any of the tissues examined. Based on the overall data, the no-observed-adverse-effect level (NOAEL) for MPH was determined to be 70 mg/kg BW/day, the highest dose tested, in both male and female rats. Highlights: 5-Methyl-2-phenyl-2-hexenal (MPH) was investigated for its 90-day subchronic toxicity. No toxicological significant changes were observed in both sexes of F344 rats up to 70 mg/kg body weight (BW)/day. The no-observed-adverse-effect level was 70 mg/kg BW/day, the highest dose tested, in both sexes.